Identification of an Optimal Cut-off for Drain Fluid Amylase on Postoperative Day 1 for Predicting Clinically Relevant Fistula After Distal Pancreatectomy: A Multi-institutional Analysis and External Validation. Issue 2 (February 2019) - Maggino, Laura; Malleo, Giuseppe; Bassi, Claudio; Allegrini, Valentina; Beane, Joal D.; Beckman, Ross M.; Chen, Bofeng; Dickson, Euan J.; Drebin, Jeffrey A.; Ecker, Brett L.; Fraker, Douglas L.; House, Michael G.; et al.
Abstract : Objective: The aim of this study was to investigate the relationship between drain fluid amylase value on the first postoperative day (DFA1) and clinically relevant fistula (CR-POPF) after distal pancreatectomy (DP), and to identify the cut-off of DFA1 that optimizes CR-POPF prediction. Background: DFA1 is a well-recognized predictor of CR-POPF after pancreatoduodenectomy, but its role in DP is largely unexplored. Methods: DFA1 levels were correlated with CR-POPF in 2 independent multi-institutional sets of DP patients: developmental (n = 338; years 2012 to 2017) and validation cohort (n = 166; years 2006 to 2016). Cut-off choice was based on Youden index calculation, and its ability to predict CR-POPF occurrence was tested in a multivariable regression model adjusted for clinical, demographic, operative, and pathological variables. Results: In the developmental set, median DFA1 was 1745 U/L and the CR-POPF rate was 21.9%. DFA1 correlated with CR-POPF with an area under the curve of 0.737 ( P < 0.001). A DFA1 of 2000 U/L had the highest Youden index, with 74.3% sensitivity and 62.1% specificity. Patients in the validation cohort displayed different demographic and operative characteristics, lower values of DFA1 (784.5 U/L, P < 0.001), and reduced CR-POPF rate (10.2%, P < 0.001). However, a DFA1 of 2000 U/L had the highest Youden index in this cohort as well, with 64.7% sensitivity and 75.8% specificity. At multivariable analysis, DFA1 ≥2000 U/L was the only factor significantly associated with CR-POPF in both cohorts. Conclusion: A DFA1 of 2000 U/L optimizes CR-POPF prediction after DP. These results provide the substrate to define best practices and improve outcomes for patients receiving DP. Abstract : Supplemental Digital Content is available in the text